PROSES INTEGRASI SIKAP DALAM PEMBELAJARAN MATEMATIKA SMP BERDASARKAN KURIKULUM 2013 (Studi Kasus pada Proses Pembelajaran Kelas VII SMP Al Azhar Syifa Budi Solo Semester Ganjil Tahun Pelajaran 2013/2014) - Sulaiman, Sulaiman; Sujadi, Imam; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objective of this research was to describe the integration process and attitude assessment done by the teacher in mathematics learning process at seventh grade of SMP Al Azhar Syifa Budi Solo. This qualitative research was a case study. The subjects of this research were a teacher and three seventh grade students of SMP Al Azhar Syifa Budi Solo. The data of integration process was in the form of activity within mathematics learning process supported by the subjectsâ statement. Data analyzing process began by assessing all data available in the recorder, which includes the learning process and interview. There were three steps in analyzing the data: data reduction, data presentation, and drawing conclusion. Information of attitude assessment was in the form of information gathering activity conducted by the teacher to the students. The data were obtained from the transcription of recorded interview and learning process. Validation techniques used were perseverance maintenance and time triangulation. The results of this research are as follows: 1) Integration process of attitude in mathematics learning at seventh grade of SMP Al Azhar Budi Syifa Solo based on Curriculum 2013. During observation learning process, the teacher asks the students to observe objects and events in daily life related to mathematics learning topic. During question and answer learning process, the teacher gives questions to the students and provides them chance to ask questions. During information gathering process, the students were asked to discuss a certain concept, to read a book and to discuss it, to examine, to explain, and to solve a problem. During associating learning process, the teacher asks the students to analyze, to associate, and to define in details the learning topic. Lastly, during communicating learning process, the teacher helps the students to summarize the material comprehensively. 2) Process of attitude assessment during mathematics learning at seventh grade of SMP Al Azhar Syifa Budi Solo are: the process of curiosity assessment was conducted by the teacher when the students solved the problems related to the materials; the process of responsibility assessment was conducted by the teacher when the students solved the problems and when the students present the result of their discussion in front of the class. The assessment of curiosity and responsibility were conducted by giving checklist mark on the attitude observation sheet.Key Words: integration process of attitude, attitude assessment process, curiosity,responsibility, curriculum 2013